0278 Isolated REM sleep behavior disorder is associated with 24-hour rhythm disruption. (25th May 2022) - Winer, Joseph; Lok, Renske; Cahuas, Ana; Bueno, Flavia; Poston, Kathleen; Mormino, Elizabeth; Zeitzer, Jamie; During, Emmanuel
Abstract: Introduction: Isolated REM sleep behavior disorder (iRBD), the loss of motor inhibition during REM sleep, is a symptom of prodromal Lewy body disease, with over 80% of iRBD patients eventually phenoconverting to Parkinson's disease or Dementia with Lewy bodies. Rest-activity rhythm disruption, also an established predictor of Parkinson's disease, has not been well characterized in patients with iRBD. Here, we tested the hypothesis that accelerometer-based measures of 24-hour rhythms would indicate greater fragmentation and variability in patients with iRBD relative to matched healthy controls. Methods: N=36 patients with iRBD recruited from the Stanford Sleep Clinic had 24-hour activity continuously monitored for (mean ± SD) 25.3 ± 8.4 days using an Axivity wristworn device. A control dataset of age, sex, and body mass index matched healthy older adults (N=126) was selected from the UK Biobank accelerometer dataset. Raw accelerometer data were processed using the GGIR, nparACT, and ActCR software packages in R, with a focus on nonparametric and 5-parameter cosinor measures of 24-hour rhythms. Functional PCA analyses (fPCA) were applied to detect overall differences in 24-hour rhythms and during sleep. Results: Patients with iRBD had lower interdaily stability and higher intradaily variability than controls (IS, Cohen's d=-1.15, Mann-Whitney test p<0.001; IV, d=0.46, p=0.04). Cosine amplitude was lower in iRBD patients (d=-0.22, p=0.001), but mean activity (mesor) did not differ (d=0.03, p=0.31), suggesting differences in rest-activity patterns rather than overall activity levels. A shape naïve approach utilizing fPCA indicated that increased activity during the night may explain overall rhythm differences observed in iRBD. Conclusion: Multiple metrics of rest-activity rhythms support the hypothesis that 24-hour rhythms are disrupted in iRBD. It remains to be determined whether rhythm fragmentation in iRBD reflects higher activity levels during REM sleep, or if dysfunctional rhythms represent the direct effects of degenerating sleep-wake regulating circuits, indicating the early stages of Lewy body disease. Support (If Any): NIA F32AG074625 to JW; NIA P30AG066515 to JW, KP, and EM